Sherris medical microbiology - Ryan, Kenneth J. (Kenneth James), 1940-; Ray, C. George, 1934- (McGraw-Hill Education Medical, 2014)
The most dynamic, comprehensive, and student-friendly text on the nature of microorganisms and the fascinating processes they employ in producing infections disease.